MANGGIS MEMBULAT TELUR DARI KALIMANTAN BARAT - Rismita Sari; M. Gafurhan (PTTI, 2013)
Among the diversity of fruits in West Kalimantan is mangosteen (Garcinia mangostana L.) in ovoid shaped and not round as in general. From the field observation, the ovoid mangosteen is distributed in several locations, namely in District Landak, Singkawang, Sambas, Bengkayang and Sanggau. Profile of the mangosteen tree which will be released as ovoid mangosteen is from Sempalai Sebedang Village, District of Sambas